Pengembangan Media Pembelajaran Fisika Menggunakan Sparkol Videoscribe - Pratiwi, Erlia Dwi; Latifah, Sri; Mustari, Mukarramah (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This research aims to; 1) the development of media physics-based sparkol videoscribe subject kinematic motion in college 2) Determine the feasibility of a medium of learning physics-based sparkol videoscribe subject of kinematics motionin college. This study is a R and D are adopting development of Borg and Gall. Subjects in this study were students and faculty at State Islamic University and the University of Muhammadiyah Metro Lampung with data collection instruments used in the form of a questionnaire given to media experts, subject matter experts, questionnaire responses of faculty and student questionnaire responses to determine the interest in learning media are developed. The type of data that is generated is qualitative data were analyzed with the guidelines the assessment criteria for determining the quality of the product. The results of this study are; 1) Generate product in the form of instructional media sparkol videoscribe physics-based motion kinematics subject in college; 2) know of quality product that has been developed is very feasible with a percentage of 86.70% based on the assessment of media experts and 84.26% by a subject matter expert in the category of very decent Response lecturer with the percentage was 93.60% in the category of very decent and student responses on physics-based learning media sparkol subject videoscribe kinematic motion with the percentage of 96.00% in college.Abstrak: Penelitian ini bertujuan untuk; mengembangkan dan mengetahui kelayakan media pembelajaran fisika berbasis sparkol videoscribe pokok bahasan kinematika gerak di perguruan tinggi. Penelitian ini merupakan penelitian R and D yang mengadopsi pengembangan dari Borg and Gall. Subjek dalam penelitian adalah dosen dan mahasiswa Universitas Islam Negeri Lampung dan Universitas Muhammadiyah Metro dengan instrumen pengumpulan data yang digunakan berupa angket yang diberikan kepada validator ahli, dosen dan mahasiswa. Jenis data yang dihasilkan adalah data kualitatif yang dianalisis dengan pedoman kriteria penilaian untuk menentukan kualitas produk. Hasil penelitian ini adalah; Menghasilkan media pembelajaran dan mengetahui kualitas produk yang telah dikembangkan 86,70% penilaian ahli media kategori sangat layak, 84,26% ahli materi kategori sangat layak, 93,60% respon dosen kategori sangat layak dan 96,00% respon mahasiswa kateori sangat layak pada media pembelajaran fisika berbasis sparkol videoscribe pokok bahasan kinematika gerak di perguruan tinggi.